Studies on protozoan parasites in angwan rogo, Jos-North Local Government of Plateau State, Nigeria (2014)
A study was carried out on the toxic and trace metal accumulation in Clarias gariepinus and Tilapia zilli from Alaro stream in Ibadan, from January 2002 to December 2003. Organs assessed were muscle, liver, bone, gills, fins and gut, while the facility used for the assessment was the inductively coupled plasma-mass spectrometer (ICP-MS) for accuracy of the results. Toxic and trace metals assessed were Sodium (Na), Magnesium (Mg), Sodium (K), Calcium (Ca), Vanadium (V), Manganese (Mn), Iron (Fe),Cobalt (Co), Nickel (Ni), Copper (Cu), Zinc (Zn), Arsenic (As), Selenium (Se), Molybdenum (Mo), Silver (Ag), Cadmium (Cd) and Lead (Pb). Toxic and trace metal levels in the liver of both fishes were significantly higher than the other tissues (P>0.05). Toxic and trace metal accumulation in the organs was found to be dependent on the concentration in the water, duration of exposure and rate of uptake of the metals. The muscle that is mainly consumed was found to be relatively low in the accumulation of the toxic and trace metals. Toxic metals such as As, Cd and Pb exceeded the guideline limit set for them by the World Health Organization (WHO). A biomonitoring program is recommended for Alaro stream due to the industrial effluents discharged into it.